A comparative analysis of different shape memory alloy actuator configurations. (July 2017) - Monteiro, Paulo Cesar C; da Silva Monteiro, Luciana Loureiro; Savi, Marcelo A; Netto, Theodoro Antoun; Pacheco, Pedro MCL; de Paiva, Tamara
Shape memory alloys are attractive engineering materials due to their potential application as actuators using the ability to memorize shapes through a thermomechanical loading. This article develops a numerical investigation of different shape memory alloy actuator configurations considering bias and antagonistic arrangements. Numerical simulations are carried out using the finite element method together with a constitutive model for shape memory alloys. Parametric analysis is carried out evaluating the performance of each actuator configuration based on stress and strain. Basically, four representative configurations of general actuators are treated: shape memory alloy wire, linear spring connected to a shape memory alloy wire, two elastic springs connected by a shape memory alloy wire, and two shape memory alloy wires connected by a spring.